1998
DOI: 10.1139/z98-099
|View full text |Cite
|
Sign up to set email alerts
|

Population differentiation in the franciscana (Pontoporia blainvillei) from two geographic locations in Brazil as determined from mitochondrial DNA control region sequences

Abstract: The franciscana, Pontoporia blainvillei, is a dolphin that experiences extensive incidental mortality in fisheries throughout its restricted distribution and is perhaps the most exploited species along the Atlantic coast of South America. However, the basic information required for effective conservation of this species is lacking. To understand the population structure of this platanistoid dolphin, we sequenced 418 base pairs (bp) of the control region and 68 bp of the adjacent pro-tRNA gene of the mtDNA from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
118
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(136 citation statements)
references
References 13 publications
15
118
0
3
Order By: Relevance
“…This suggested a model based upon a single sample of both sexes, with its increased precision due to larger sample size, may be preferable. Several morphometric and genetic studies (Pinedo, 1991(Pinedo, , 1995Secchi et al, 1998Secchi et al, , 2003aOtt et al, 2002;Ramos et al, 2002;Lázaro et al, 2004;Barreto and Rosas, 2006) have established the existence of three franciscana morphotypes/genotypes: one found in FMA I (Rio de Janeiro and Espírito Santo states, Brazil); a second one in FMA II (from São Paulo to Santa Catarina states, Brazil) and the third in FMA III and IV (from Rio Grande do Sul state, Brazil down to Buenos Aires Province, Argentina). Animals inhabiting FMA I are smaller than animals from FMA III and IV but larger than those from FMA II.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested a model based upon a single sample of both sexes, with its increased precision due to larger sample size, may be preferable. Several morphometric and genetic studies (Pinedo, 1991(Pinedo, , 1995Secchi et al, 1998Secchi et al, , 2003aOtt et al, 2002;Ramos et al, 2002;Lázaro et al, 2004;Barreto and Rosas, 2006) have established the existence of three franciscana morphotypes/genotypes: one found in FMA I (Rio de Janeiro and Espírito Santo states, Brazil); a second one in FMA II (from São Paulo to Santa Catarina states, Brazil) and the third in FMA III and IV (from Rio Grande do Sul state, Brazil down to Buenos Aires Province, Argentina). Animals inhabiting FMA I are smaller than animals from FMA III and IV but larger than those from FMA II.…”
Section: Discussionmentioning
confidence: 99%
“…Pinedo (1991) Secchi et al (1998) examined mitochondrial DNA from individuals of these two forms and also found significant differences between them. Both studies suggested that the two populations should be treated as separate management units.…”
Section: Lessons From Monitoring Praia Grande Fisherymentioning
confidence: 99%
“…The results were compared with those published by Secchi et al (1998), which included animals from Rio Grande do Sul (GS 9 and 10) and Rio de Janeiro (GS 3). Lázaro suggested that franciscanas from Rio Grande do Sul, Uruguay and Argentina may belong to a single large genetic population.…”
Section: Biology and Ecologymentioning
confidence: 99%
“…She also presented the results of a comparative analysis of mtDNA control region sequences between these animals and those from Rio Grande do Sul and Rio de Janeiro analysed by Secchi et al (1998). The results indicated that individuals from Paraná were more similar to those of Rio Grande do Sul than to those of Rio de Janeiro and that the population off Rio de Janeiro may be isolated.…”
Section: Biology and Ecologymentioning
confidence: 99%